Deciphering the Behavioral Response of Meloidogyne incognita and Fusarium oxysporum Toward Mustard Essential Oil - Dutta, Anirban; Mandal, Abhishek; Kundu, Aditi; Malik, Monika; Chaudhary, Amrendra; Khan, Matiyar Rahaman; Shanmugam, Veerubommu; Rao, Uma; Saha, Supradip; Patanjali, Neeraj; Kumar, Rajesh; Kumar, Anil; et al. (Frontiers in Plant Science, 2021)
Environmental concerns related to synthetic pesticides and the emphasis on the adoption of an integrated pest management concept as a cardinal principle have strengthened the focus of global research and development on botanical pesticides. A scientific understanding of the mode of action of biomolecules over a range of pests is key to the successful development of biopesticides. The present investigation focuses on the in silico protein-ligand interactions of allyl isothiocyanate (AITC), a major constituent of black mustard (Brassica nigra) essential oil (MEO) against two pests, namely, Meloidogyne incognita (Mi) and Fusarium oxysporum f. sp. lycopersici (Fol), that cause severe yield losses in agricultural crops, especially in vegetables. The in vitro bioassay results of MEO against Mi exhibited an exposure time dependent on the lethal concentration causing 50% mortality (LC50) values of 47.7, 30.3, and 20.4 μg ml−1 at 24, 48, and 72 h of exposure, respectively. The study revealed short-term nematostatic activity at lower concentrations, with nematicidal activity at higher concentrations upon prolonged exposure. Black mustard essential oil displayed excellent in vitro Fol mycelial growth inhibition, with an effective concentration to cause 50% inhibition (EC50) value of 6.42 μg ml−1. In order to decipher the mechanism of action of MEO, its major component, AITC (87.6%), which was identified by gas chromatography–mass spectrometry (GC-MS), was subjected to in silico docking and simulation studies against seven and eight putative target proteins of Mi and Fol, respectively. Allyl isothiocyanate exhibited the highest binding affinity with the binding sites of acetyl cholinesterase (AChE), followed by odorant response gene-1 (ODR1) and neuropeptide G-protein coupled receptor (nGPCR) in Mi, suggesting the possible suppression of neurotransmission and chemosensing functions. Among the target proteins of Fol, AITC was the most effective protein in blocking chitin synthase (CS), followed by 2,3-dihydroxy benzoic acid decarboxylase (6m53) and trypsinase (1try), thus inferring these as the principal molecular targets of fungal growth. Taken together, the study establishes the potential of MEO as a novel biopesticide lead, which will be utilized further to manage the Mi–Fol disease complex.